2018
DOI: 10.1177/2041669518774069
|View full text |Cite
|
Sign up to set email alerts
|

Vection Is Enhanced by Increased Exposure to Optic Flow

Abstract: We examined whether vection strength could be modulated by altering the exposure duration to optic flow. Experiment 1 sourced 150 different video clips from various Japanese animation works which simulated self-motion. Despite large differences in the content of these video clips, we found a significant positive correlation between their play durations and their ratings of vection magnitude. Experiment 2 examined this relationship further using more tightly controlled visual motion stimuli. Vection was induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Thus, if participants perceived that they were moving about half as much as natural self-motion, they would rate vection strength as “50.” They were allowed to choose a rating greater than 100 if necessary, but none of them did so. This method is the same as we have used in several studies (Fujii, Seno, & Allison, 2018; Seno et al., 2010, 2017, 2018; Seno, Palmisano, Riecke, & Nakamura, 2015) and has been confirmed to be valid for evaluating vection strength.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, if participants perceived that they were moving about half as much as natural self-motion, they would rate vection strength as “50.” They were allowed to choose a rating greater than 100 if necessary, but none of them did so. This method is the same as we have used in several studies (Fujii, Seno, & Allison, 2018; Seno et al., 2010, 2017, 2018; Seno, Palmisano, Riecke, & Nakamura, 2015) and has been confirmed to be valid for evaluating vection strength.…”
Section: Methodsmentioning
confidence: 92%
“…They were allowed to choose a rating greater than 100 if necessary, but none of them did so. This method is the same as we have used in several studies (Fujii, Seno, & Allison, 2018;Seno et al, 2010Seno et al, , 2017Seno et al, , 2018; Seno, Figure 1. The stimulus used in Experiment 1 and Experiment 2.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In our set‐up, vection was elicited with relatively short stimulus duration of 5 s, whilst many previous experiments have employed longer durations e.g. 10 s and have found that vection becomes stronger with exposure duration (Palmisano & Riecke, ; Seno et al., ). The short vection onset latency may be due to the particular stimulus motion characteristics or the fact that participants were standing.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the past behavioral research on vection has focused on its time course. When a vection-inducing display is presented to a stationary observer, there is typically a finite delay before any illusory self-motion is reported (e.g., Brandt et al, 1973;Dichgans and Brandt, 1978;Seno et al, 2017Seno et al, , 2018Telford and Frost, 1993;Warren, 1995). This vection onset latency is often measured as the time interval from the start of the optic flow until the participant first presses a button.…”
Section: Introductionmentioning
confidence: 99%